2016
DOI: 10.1098/rsta.2015.0125
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the in meso crystallization mechanism by characterizing the lipid mesophase microenvironment during the growth of single transmembrane α-helical peptide crystals

Abstract: The proposed mechanism for in meso crystallization of transmembrane proteins suggests that a protein or peptide is initially uniformly dispersed in the lipid self-assembly cubic phase but that crystals grow from a local lamellar phase, which acts as a conduit between the crystal and the bulk cubic phase. However, there is very limited experimental evidence for this theory. We have developed protocols to investigate the lipid mesophase microenvironment during crystal growth using standard procedures readily ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The first X-ray structure of an MP extracted and purified as a SMALP was reported by Broecker et al [23]. SMA-purified recombinant microbial rhodopsin (bR), a seven-transmembrane α-helical MP, was crystallized using the lipidic cubic phase (LCP) method [24] resulting in a structure of 2.0 Å resolution. This comparative study undertook the parallel LCP crystallisation of both SMA- and detergent-purified bR.…”
Section: Latest Applications Of Smalpsmentioning
confidence: 99%
“…The first X-ray structure of an MP extracted and purified as a SMALP was reported by Broecker et al [23]. SMA-purified recombinant microbial rhodopsin (bR), a seven-transmembrane α-helical MP, was crystallized using the lipidic cubic phase (LCP) method [24] resulting in a structure of 2.0 Å resolution. This comparative study undertook the parallel LCP crystallisation of both SMA- and detergent-purified bR.…”
Section: Latest Applications Of Smalpsmentioning
confidence: 99%
“…This suggested that the specific mechanism is peptide and protein dependent (van 't Hag et al, 2019 ). This was the first time in meso crystallization was studied from the protein-eye perspective as previous studies using SAXS and SANS without contrast-matching focused, by necessity, on the lipid phase (Efremov et al, 2005 ; van 't Hag et al, 2016c ; Zabara et al, 2017 ).…”
Section: Time-resolved Studies On Multi-component Systems Using Sansmentioning
confidence: 96%
“…Based on recent computational models of IMP incorporation in lipid mesophases, it has been suggested that lamellar structures provide a more favorable environment for oligomerization (a prelude to nucleation and crystal growth) compared to cubic mesophases, because of increased hydrophobic mismatch between the protein and the lipid bilayer with lamellar structures . In the past 3 years, synchrotron small-angle X-ray scattering (SAXS) studies that investigated the lipid microenvironment around growing DAP12 and intimin crystals , suggested that a transient lipid lamellar L α phase is present during crystal nucleation, facilitating the initial build-up of protein molecules. Crystals were proposed to phase separate from the lipid phase once they were larger than the domain size (∼1 μm) of the cubic Q II phase.…”
Section: Introductionmentioning
confidence: 99%
“…(B) DAP12 tetrameric crystal structure at 2.1 Å resolution with a layered spacing of 50.6 Å (PDB ID 4WO1). , (C) Glycophorin A crystal structure at 1.9 Å resolution with a layered spacing of 46.9 Å (PDB ID 5EH6). In (B) and (C) side-views show type I packing of one symmetric unit in red and symmetry mates in gray.…”
Section: Introductionmentioning
confidence: 99%